(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Type 2 diabetes mellitus (T2DM) is a metabolic disease that affects both young and old people. The prevalence of T2DM is increasing worldwide and is reaching epidemic proportions. It is associated with a dysregulation of lipid metabolism that favors the development and progression of many diseases, including diabetic dyslipidemia. Therefore, in-depth studies are needed to understand the epigenetic mechanisms of diabetic dyslipidemia, especially at the molecular level. However, the underlying mechanisms are still largely unknown. In the current investigation, we aimed to elucidate novel potential lipid metabolism-related long non-coding RNAs (lncRNAs) that regulate diabetic dyslipidemia development and provide novel signatures for its prognosis and precise treatment. HbA1c levels and lipid profiles were analyzed in 71 T2DM patients and 32 non-diabetic controls using established assays. The expression patterns of the genes GHRLOS, lnc-GHRL-3:3, and LINC00852 were detected by quantitative real-time polymerase chain reaction (qRT-PCR).The results showed that the expression levels of the lncRNAs GHRLOS, lnc-GHRL-3:3, and LINC00852 were significantly (P < 0.0001) higher in diabetics compared to non-diabetics. Pearson’s correlation analysis showed that the expression levels of GHRLOS, lnc-GHRL-3:3, and LINC00852 were significantly and negatively correlated with HbA1c, TC, TG, LDL, and VLDL and positively correlated with HDL. The results of the linear regression analysis confirmed the correlation in the same direction and the significance value of Pearson coloration coefficient analysis. Finally, it can be concluded that the lncRNAs GHRLOS, lnc-GHRL-3:3, and LINC00852 show a significant correlation with dyslipidemia in T2DM patients, indicating their potential roles as biomarkers and regulators of diabetic dyslipidemia.